Problems of Parents in Accompanying Learning Activities at Primary school children - Khovivah Nilva Satrina; Andi Suhandi; Issaura Sherly Pamela (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study Problems of Parents in Accompanying Learning Activities at Primary school children to describe the problems of parents in assisting learning activities in elementary school children.This study aims to describe the problems of parents in assisting learning activities in elementary school children. This research is a qualitative research with the type of phenomenological research. Sources of data in this study were parents of third grade students at SD Negeri 45/1 Sridadi. Data collection techniques carried out in this study used observations, interviews, and documentation techniques. The data obtained were analyzed in several stages, namely data reduction, data presentation and then conclusions were drawn and data verification. Testing the validity of the data is done by triangulation. The results of this study indicate that: The problems of parents in assisting children's learning activities are, first, parents who do not have time to accompany and guide children to study at home, because parents have other activities such as working and earning a living. Second, the lack of full mastery of the material by parents due to differences in the curriculum and also the minimal level of parental education that hinders and is less than optimal in guiding children. Third, difficulties in operating gadgets and providing internet quota for online learning. Fourth, parents have difficulty in increasing interest and growing motivation to learn in children because children who do not have the intention from within themselves to learn and also children play more often than learn. The conclusion obtained from this study is that parenting does not always run smoothly, but there are obstacles or problems with parents in assisting children's learning. From the results of the study, it is hoped that parents will be able to maximize their assistance in children's learning activities so that learning objectives can be achieved as expected.